MEDICAL TREATMENT OF CHRONIC THROMBOEMBOLIC PULMONARY HYPERTENSION - K. V. Mershin; T. V. Martynuk (Евразийский Кардиологический Журнал)
CTEPH is the only type of surgically curable pulmonary arterial hypertension. In spite that, up to 50% of all CTEPH patients are rejected of surgical treatment because of distal lesions of pulmonary arteries or because of other contraindications. Medical treatment was proven to be one of the options to support this cohort of patients. Recent clinical studies addressed some medication regimens for treatment of CTEPH patients and showed distinct changes of different PH-variables with time. We discuss the main principles of drug therapy for inoperable CTEPH as well as for patients awaiting surgery, during and after pulmonary thrombo-endarterectomy.